2003
DOI: 10.1525/as.2003.43.3.507
|View full text |Cite
|
Sign up to set email alerts
|

China-Asean Free Trade Agreement: Shaping Future Economic Relations

Abstract: The China-ASEAN Free Trade Agreement has been hailed as a landmark pact in pushing for freer trade between China and the ASEAN countries. With the establishment of the free trade zone, trade and investment between the Chinese and ASEAN economies are expected to increase significantly; but while the economic benefits are inexorable, the extent of gains derived from closer integration hinges on the Sino-ASEAN economic relationship, which is both complementary and competitive in nature. At the present stage of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 3 publications
2
16
0
Order By: Relevance
“…Broadly speaking, the position change is due to the downward trend in comparative advantage and the trade balance of each country. This result is supported by the findings of Wong and Chan (2003) who found that initially the economies of ASEAN countries (except Singapore) were based on natural resources (economic growth dependent on natural resource exports and primary products) which since 2001 ASEAN trade has shifted from primary products to processed products.…”
Section: Discussionsupporting
confidence: 63%
“…Broadly speaking, the position change is due to the downward trend in comparative advantage and the trade balance of each country. This result is supported by the findings of Wong and Chan (2003) who found that initially the economies of ASEAN countries (except Singapore) were based on natural resources (economic growth dependent on natural resource exports and primary products) which since 2001 ASEAN trade has shifted from primary products to processed products.…”
Section: Discussionsupporting
confidence: 63%
“…As mentioned earlier, Lao Cai is the most important border city between Vietnam and China. Despite a long history of tensions and conflicts (Womack 2006), China is an essential economic partner of Vietnam, and these exchanges are reinforced by the agreements between China and ASEAN (Wong and Chan 2003). Hence, the national authorities consider it crucial to facilitate trade between the two countries; the opening of the highway between Hai Phong, Hanoi and Lao Cai (and going further to Kunming, see Figure 2) being a major milestone to this end.…”
Section: The Environmental Protection Policies and The Bureaucracy: Amentioning
confidence: 99%
“…Although China and ASEAN lacked strong 'natural' economic complementarities (Wong and Chan, 2003), trade increased more than six-fold in the decade following China's 2000 proposal and cumulative reciprocal foreign direct investment (FDI) rose dramatically (ASEAN Secretariat, 2009). However, it is also important to note that the trade and investment totals between China and Southeast Asia pale in comparison to the massive and rapidly expanding economic linkages between China, Japan and South Korea, not to mention between the Chinese Mainland and Taiwan (UNCTAD, 2004).…”
mentioning
confidence: 99%